A NEW CU-BASED SMA WITH EXTREMELY HIGH MARTENSITIC-TRANSFORMATION TEMPERATURES - Guilemany, J. M.; Fernandez, J.; Franch, R.; Benedetti, Assis Vicente [UNESP]; Adorno, A. T. (Editions Physique, 1995)
A new series of high temperature copper based shape memory alloys has recently been patented. These alloys contain 8-20 wt% Al, 1-20 wt% Ag, 0-2 wt% of a minor element (preferably Co), balance copper. The martensitic start transformation temperatures of these alloys are above 200 degrees C and, in some cases, they have good high temperature stability and may be useful in commercial applications where higher operating temperatures than those obtained from Cu-Zn-Al and Cu-Al-Ni shape memory alloys are required.